Peran Pendidikan Kewirausahaan dalam Strategi Pengembangan UMKM Sebagai Pendorong Perekonomian Indonesia - Ahmad Yusuf Akbar; B. Miftahulzannah Siregar; Syahrina Aisyah Lubis; Reni Ria Armayani Hasibuan (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a strategic role as the backbone of Indonesia’s economy through their significant contribution to employment creation and Gross Domestic Product (GDP). However, many MSMEs continue to face structural challenges, including limited managerial capacity, low levels of innovation, and weak adaptation to digital transformation. In response to these challenges, entrepreneurship education has emerged as a strategic instrument for strengthening MSME competitiveness and sustainability. This study aims to analyze the role of entrepreneurship education as a development strategy for MSMEs in supporting Indonesia’s economic growth. Employing a descriptive qualitative approach with a case study design, this research examines several MSMEs that have participated in entrepreneurship education and training programs organized by government and educational institutions. The findings reveal that entrepreneurship education contributes to strengthening entrepreneurial mindset, improving managerial and financial skills, encouraging business innovation, and enhancing digital technology adoption among MSME actors. Moreover, entrepreneurship education supports business resilience and market expansion, enabling MSMEs to adapt to dynamic economic conditions. These findings indicate that entrepreneurship education is not merely a capacity-building tool, but a strategic policy instrument for developing competitive and sustainable MSMEs. Therefore, the institutionalization of integrated and continuous entrepreneurship education is essential to optimize the role of MSMEs in fostering inclusive and sustainable economic growth in Indonesia.